Well-being and academic attitudes among secondary school students living in a context of life-threatening collective violence in Northern Nigeria - Shockden, Eric Isaac; Bahago, Beatrice A.; Omede, Jacob (Frontiers in Education, 2023)
Collective violence limits well-being and academic achievement among the millions of young people in low- and middle-income countries who are exposed to armed conflict, terrorism, harassment, kidnapping, and other forms of communal violence. Most past research has focused on survivors or witnesses, neglecting the much larger number of young people who live under the prolonged threat of violence. This study addressed this gap by applying the Situated Expectancy-Value Model of adolescent academic achievement. This informed predictions about the relationship between well-being and adolescents’ orientation to formal education in a context of collective violence in which schools are a special target. Over the past decade, Northern Nigeria has experienced recurring terrorist attacks and large-scale abductions of school students. Students attending public secondary schools in Northern Nigeria (n = 371; male = 45.6%, age range = 16–17; mean age = 16.7 years) completed three questionnaires that assessed four domains of well-being (body image, self-esteem, a positive social orientation, and positive emotions), the perceived value of academic learning, and two behaviours strongly related to academic achievement (persistence and engagement). Multiple regression analyses found that the four domains of well-being accounted for 70.5%, 87.3%, and 88.3% of variance in the perceived value of academic learning, academic persistence, and academic engagement, respectively. Subsequent analyses revealed that the associations between multi-dimensional well-being and both persistence and engagement were partially mediated by the perceived value of academic learning. In summary, although the observational research design precluded conclusions about the direction of effect in associations between the variables, the results are consistent with the interpretation that psychological well-being allows students to appreciate the value of academic learning, and this contributes to higher academic engagement and greater persistence on academic tasks.